Nonsurgical Management of an Extensive Perforative Internal Root Resorption with Calcium-Enriched Mixture Cement - Esnaashari, Ehsan; Pezeshkfar, Arezou; Fazlyab, Mahta (Iranian Endodontic Journal, 2014)
Internal inflammatory root resorption (IIRR) is a rare condition of the root canal and if it is left untreated it may lead to destruction of the surrounding dental hard tissues. Odontoclasts are responsible for this situation which can potentially perforate the root. Many initiating factors have been mentioned for IIRR, almost all causing chronic inflammation in the vital pulp. IIRR is usually symptom free, but in cases of root perforation, a sinus tract usually forms. The prognosis of treatment depends on the size of lesion with small lesions being managed with good prognosis. However, in case of notable destruction of the tooth, the prognosis is poor and tooth extraction may become inevitable. This report represents the management of an extensive perforative IIRR that was successfully sealed with calcium-enriched mixture (CEM) cement. After 12 months the tooth was still symptomless and in function.